Cryptochrome genes mediate photoperiodic responses in the cricket Modicogryllus siamensis. (24th July 2018) - Ueda, Haruki; Tamaki, Saori; Miki, Taiki; Uryu, Outa; Kamae, Yuichi; Nose, Motoki; Shinohara, Tsugumichi; Tomioka, Kenji
Abstract: Diapause is a strategy used by many insects living in temperate zones to survive the winter. The most reliable environmental cue to induce diapause is photoperiod, for which day or night length is measured by a mechanism called the photoperiodic clock. Despite several studies in insects, the photoperiodic mechanisms remain unclear. In the present study, we show that cryptochrome s ( cry s) mediate photoperiodic responses in the cricket Modicogryllus siamensis . Nymphal development of M. siamensis is highly dependent on photoperiod: under long‐day conditions, most nymphs become adults within 60 days after hatching by undergoing seven moults, whereas, under short‐day conditions, they take much longer (approximately 180 days), with an increased number of moults. Similar to most insects, the cricket has two cry genes: the Drosophila type cry ( Ms'cry1 ) and the mammalian type cry ( Ms'cry2 ). Ms'cry1 shows some constitutive expression, whereas Ms'cry2 is rhythmically expressed under both long‐day and short‐day conditions. Parental RNA interference against either or both of the two cry genes partially prevents the long‐day responses, whereas inhibition of Ms'cry1 or Ms'cry1 / Ms'cry2 enhances the short‐day response with a further delay of adult emergence or its complete prevention, respectively. Nymphal RNA interference of Ms'cry s at the fourth‐instar stage delays adult emergence and increases the number of moults under long‐day conditions. We hypothesize that Ms'cry genes are involved not only in the photoperiodic mechanism, but also in the regulatory mechanism of nymphal development downstream of the photoperiodic clock in the cricket M. siamensis . Abstract : Parental RNA interference against either or both of Ms'cry1 and Ms'cry2 partially prevents long‐day responses, whereas inhibition of Ms'cry1 or Ms'cry1 / Ms'cry2 enhances or completely prevents short‐day responses, respectively, in Modicogryllus siamensis . Nymphal RNA interference of Ms'cry s at the fourth‐instar stage delays adult emergence and increases the number of moults under long‐day conditions. Ms'cry genes are probably involved not only in the photoperiodic mechanism, but also in the regulatory mechanism of nymphal development downstream of the photoperiodic clock in M. siamensis .